Phosphoric Acid Doped Crosslinked Polybenzimidazole/Modified Graphene Oxide Composite Membranes for High Temperature Proton Exchange Membrane Applications. Issue 11 (1st January 2018) - Cai, Yangben; Yue, Zhouying; Teng, Xin; Xu, Shiai
Abstract : A radiation grafting graphene oxide reinforced polybenzimidazole (PBI-RGO) was fabricated and then crosslinked with a self-made crosslinker containing benzimidazole groups by a facile method to obtain crosslinked PBI/RGO (cPBI/RGO) membrane, which was further doped with phosphoric acid (PA) for high temperature proton exchange membrane (HT-PEM) applications. The introduction of benzimidazole groups in the crosslinker results in an increase in PA uptake from 222% to 303% and a reduction of tensile strength of the membrane. The crosslinking structure can effectively improve the tensile strength compared with uncrosslinked membrane at the same PA uptake. The crosslinked membrane shows higher remaining weight after immersion in Fenton's solution for 6 days and PA for 8 days than uncrosslinked membrane, indicating that it has better oxidative and chemical stability. The introduction of RGO and the crosslinking structure can also improve the proton conductivity of membrane. The proton conductivity of PA-doped cPBI/RGO membrane is 58.6 mS·cm −1 at 170°C without humidity, which is increased by 2.6 times compared with that of PA-doped PBI membrane. The crosslinking structure allows the membrane to have better stability and higher proton conductivity, thus making it suitable for HT-PEM applications.